North–South divide: Distribution and outcome of respiratory viral infections in paediatric intensive care units in Cape Town (South Africa) and Nottingham (United Kingdom). (23rd December 2013) - Lonngren, Camilla; Morrow, Brenda M; Haynes, Sarah; Yusri, Taha; Vyas, Harish; Argent, Andrew C
<x xml:space="preserve">Abstract</x> Aim This study aims to describe and compare the spectrum, course, seasonality and outcome of children with virus‐associated respiratory symptoms (VARS) admitted to two paediatric intensive care units (PICUs) in the United Kingdom (UK) and South Africa (SA). Methods Cross‐sectional study of routinely collected data on subjects admitted to PICU with respiratory symptoms and positive respiratory viral polymerase chain reaction between July 2009 and July 2011. Results Six hundred forty‐six samples yielding 765 viral isolates (74% from SA) from 599 patients (53% male; median (interquartile range) age 6.0 (2.3–16.5) months) were included. Rhinovirus, respiratory syncytial virus and adenovirus were most commonly isolated. Adenovirus was more prevalent in SA (24.3% vs. 16.8%, P = 0.03). Possible or likely nosocomial viral acquisition occurred in 78% of isolates in SA versus 48% in the UK (P < 0.0001).Total mortality was 13.5%; 17% in SA versus 4% in the UK (P < 0.0001). Mortality for community acquired VARS was 8.4% versus 16.1% in those with possible nosocomial viral acquisition (P = 0.009). Factors independently associated with mortality were: SA study site (adjusted odds ratio (OR) 3.4, 95% confidence interval (CI) 1.4–8.5; P = 0.008); age (months) (OR 1.0, 95% CI 1.0–1.02; P = 0.001); Paediatric Index of Mortality 2 score (%) (OR 1.0, 95% CI 1.01–1.03; P = 0.0002) and isolation of adenovirus (OR 3.0, 95% CI 1.8–5.0; P < 0.0001). Conclusions The outcome of children with VARS was worse in SA compared with the UK PICU. Nosocomial VARS was highlighted as an important concern and requires further investigation.